Peningkatan Kompetensi Metodologis Mahasiswa Melalui Sosialisasi Teknik Efektif Penelitian Kualitatif - Lukman Dahlan; Rahayu Alkam; Febrina Nur Ramadhani; Andi Muhammad Syukur Hidayatullah; Wina Ayudia Akbar (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity was conducted to enhance accounting students’ methodological literacy toward qualitative research, which remains less popular within the Faculty of Economics and Business, Universitas Negeri Makassar (FEB UNM). Field observations revealed that most accounting students prefer quantitative approaches in their undergraduate theses, considering them easier and more measurable. Therefore, the implementing team organized a qualitative research methodology socialization program for sixth-semester students who are preparing for their final research projects. The activity employed an interactive lecture and open discussion method, and its effectiveness was assessed through a comparison of pre-test and post-test results. The findings indicated an overall improvement in students’ conceptual understanding across all measured aspects, with the highest increase in data collection techniques (11.76%) and the lowest in understanding the researcher’s role as the main instrument (5.88%). These results demonstrate that conceptual-based socialization is effective in improving students’ methodological comprehension and academic awareness of qualitative research. The program is expected to continue as a sustainable initiative to strengthen the research culture and broaden methodological perspectives among accounting students at FEB UNM.